Analyzing Taiwan’s patenting performance: Comparing US patents and triadic patent families - Chen, Dar-Zen; Huang, Wei-Tzu; Huang, Mu-Hsuan; Chen, Dar-Zen; Huang, Wei-Tzu; Huang, Mu-Hsuan (Malaysian Journal of Library and Information Science, 2017)
Chen, D. Z., Huang, W. T., & Huang, M. H. (2014). Analyzing Taiwan’s patenting performance: Comparing US patents and triadic patent families. Malaysian Journal of Library & Information Science, Vol.19, no. 1: 51-70. Issued patents are frequently maneuvered as indicators for measuring innovative technology development. These indicators are usually used by many internationally-renowned ranking institutions to measure innovative activities at country level. In those ranking results, Taiwan exhibits inconsistent performance by different indicators, ranking fourth by the number of USPTO-granted patents (US patents) but twenty-second by the number of triadic patent families (TPF). This study adopts a statistical method to verify Taiwan’s patent performance as outlier among 40 major countries. We endeavor to explain the discrepancy between US patents and triadic patent families. Compared to other countries, Taiwan’s ration of patents in triadic patent families to the US patent is lower than 40 countries in all technology fields. Moreover, Taiwan’s international trading relationship with the US, Japan, and European Union cannot explain its extreme patenting performance. The study finds out that without a membership in Patent Cooperation Treaty (PCT,) Taiwan tends to shoulder more cost in applying multilateral patents, which may affect its quantity of patents in the European Patent Office (EPO) and Japan Patent Office (JPO), as well as the performance of TPF.